ADVANCEMENTS IN HADITH AUTHENTICATION METHODS: A SYSTEMATIC LITERATURE REVIEW - MOHAMAD KHALID BAHRUDIN; ISHAK SULIAMAN; MOHAMAD AZRIEN MOHAMED ADNAN (Hamdard Islamicus, 2025)
Since the commencement of hadith as one of the Islamic branches of knowledge, scholars had given a lot of attention on the authentication process of hadith corpus. This is to avoid the exploitation or dissemination of non-authentic hadiths that can divert the society from the true Islamic practices. With that being said, little work has been done on systematic review on the hadith authentication methods. Therefore, this study discusses a Systematic Literature Review (SLR) related to the topic. A total 115 literatures were identified from the initial searching process. The number was eventually reduced to 53 after screening and qualification evaluation process. This study found that the methods divided into two themes: information and communication technology (ICT) and conventional method. Under these themes, there are topics and sub-topics that further detailed the process of hadith authentication. The study identified several limitations such as the imbalance between methods of authentication, incomprehensive manipulation of data set, and the absence of authentication methods developed for a specific group of people.